Features of formation of the automobile and highway industryfuture specialists’ social responsibility - Sozykina, G. S. (Problems of Engineer-Pedagogical Education, 2018)
The specificity of social responsibility of the automobile and highway industry future specialists is studied in the article. The variety of views on the phenomenon of social responsibility in the scientific sources is emphasized. Despite the absence of a generally accepted approach to determining the essence of social responsibility, it is noted that it takes a significant place in the system of the personality’s values and attidues. The essence of this concept as the specialist’s integrative quality that determines his behavior based on understanding and acceptance of social norms and values, knowledge about social responsibility, rights and duties, the ability to assess the impact and results of their own actions is specified. The need to improve social responsibility of the specialists of the industry because of the critical state of national roads is emphasized. Some methods of forming the mentioned feature through various forms of students’ educational and social activities, the use of active methods, and implementation of new technologies into the process of education are described.